Where there's a will - Mortimer, John Clifford 1923-2009 (Viking, 2005)
The author ponders the non-material legacy he hopes to leave to the next generation, sharing humorous thoughts about the pleasures he has experienced through drink, outdoor sex, and his vision of God as the "Grand Perhaps."
Keywords: Conduct of life -- Humor; English essays